Unsur-Unsur Intrinsik Cerpen “Al-Ufuqu Wara´A Al-Bawwabati” Dalam Ardu Al-Burtuqali Al-Hazini Karya Gassan Kanafani: Analisis Struktural Stanton - FAHMI, Achmad ([Yogyakarta] : Universitas Gadjah Mada, 2014)
“al-Ufuqu Wara>´a al-Bawwa>bati” short story in Ardu al-Burtuqa>li al- H}azi>ni short stories anthology is a one of short stories by Palestinian Writer, Gassa>n Kanafa>ni>. The aim of this study is to identify intrinsic elements of this short story by structural analysis method of Stanton. Intrinsic elements in this study consist of characters and characterizations, plot, setting themes, point of view, style and tones, title, symbolism, and theme. These elements are identified the described so that can be determined the relationship between elements to gain a unified whole meaning of this elements. The result of the study showed that character of “al-Ufuqu Wara>´a al- Bawwa>bati” short story consist of main character and additional character. The main character is ‘Ali> and the additional character is Dalla>l, his mom, his aunt. The plot is assorted plots that consist of sequence of beginning, middle, and end; and setting themes is Palestine 1948-1958 with occupied of Palestine land by Israel. The theme of the story is honest to tell the truth can end the suffering of somebody else. The story was narrated with omniscient point of view with descriptive language styles and dramatic ironic tones. The symbolism “al-Ufuqu Wara>´a al-Bawwa>bati” short story are refers to Mandilbaum gate. All of the elements have relation that makes a unified whole meaning.